If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -57 = 9p + 10 Reorder the terms: -57 + 8p = 9p + 10 Reorder the terms: -57 + 8p = 10 + 9p Solving -57 + 8p = 10 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -57 + 8p + -9p = 10 + 9p + -9p Combine like terms: 8p + -9p = -1p -57 + -1p = 10 + 9p + -9p Combine like terms: 9p + -9p = 0 -57 + -1p = 10 + 0 -57 + -1p = 10 Add '57' to each side of the equation. -57 + 57 + -1p = 10 + 57 Combine like terms: -57 + 57 = 0 0 + -1p = 10 + 57 -1p = 10 + 57 Combine like terms: 10 + 57 = 67 -1p = 67 Divide each side by '-1'. p = -67 Simplifying p = -67
| 120=.8x | | -4x^2+29x-25=0 | | (sec^2)(x)=7 | | 47-12=5(x-2) | | x^3-3y^3-9z^3=0 | | x+3.5x=90 | | 1566=29(p+20) | | x+x+15+x+75=180 | | 14x=11x+33 | | x+18+3x=-20-3x-25 | | 14x=11x+34 | | 14x=11x+36 | | 14x=11x+41 | | 14x=11x+61 | | -1/5b-2/5=-3 | | 11x=3y-3 | | x^2-6x=135 | | 12t^2-18t+7=0 | | 14x=11x+81 | | 180=x+(2x)+(x-20) | | 23-48=3(x-1)-4 | | 10x/11 | | f(-2)=3x^2+7x-12 | | y-2=x^2-3x+7 | | B/14-b/22 | | 5(2x+10)+1= | | au^2+bu+c=0 | | cosine(2x)+7sin+3=0 | | f(7)=3x^2+7x-12 | | 38-n=-8(1+3n) | | -8x^2+58x-50=0 | | 8(n+5)=-2n+20 |